A novel spatial parallel multi-stable mechanism with eight stable states. (May 2023) - Guo, Fan; Sun, Tao; Wang, Panfeng; Liu, Shibo; Li, Jiaxing; Song, Yimin
Highlights: A SPMM with eight stable equilibrium states is proposed. The kinetostatic model and the multi-stability topologies of SPMM are developed. The stabilities and switching paths are verified by experiments. Abstract: A multi-stable flexible mechanism is a mechanical device that can switch to different stable equilibrium states under external power. Most existing multi-stable mechanisms are achieved by splicing bi-stable mechanisms. This paper proposes a novel Spatial Parallel Multi-stable Mechanism (SPMM) without bi-stable mechanisms connected, which even could achieve eight stable equilibrium states and meanwhile contain bi-stable mechanisms' advantages such like simple structure and reliable abilities. To identify the equilibrium states, the paper develops a kinetostatic model using the Energy-Kinematics Differential Equations (EKDE) for the proposed SPMM. Based on the equilibrium states, the multi-stability topologies are drawn referring to direct groups, including the distribution of various equilibrium states and the switching paths between every two stable states. At last, the paper shows the experimental results of a 3D printed prototype and verify the eight-stability behaviors and the switching paths through unstable equilibrium states. A concept of the application in deformable cable protection shell using the SPMM is introduced.